KEMAMPUAN MENULIS KARANGAN PERSUASI SISWA KELAS X SMAN 1 KABUPATEN SOLOK SELATAN - Putri, Dainur (AT-TALIM, 2012)
The purpose of this study was to describe how the ability to write a persuasive essay in class X students of SMAN 1 South Solok seen from the characteristics of persuasive essay that contains an invitation, containing facts, logical sentences, and trustworthy. The method used in this research is descriptive method. Data collection techniques used in this research is a test post. Findings showed that there were 28 essays written by the students, which amounted to 21 perfectly qualified individuals with high mastery 96% - 100%, 5 people who get close enough to the qualification level of mastery of 46% - 55%, and 2 people are getting poor qualifier with mastery level 16 % - 25%, and the level of class X students of SMAN 1 South Solok in writing a persuasive essay in terms of the characteristics of persuasion that contains an invitation, containing facts, logical sentences, and trustworthy quite well with the average value of 86% (level of mastery 86% - 95%).